HUBUNGAN MODEL PEMBELAJARAN KOOPERATIF TIPE PROBLEM-BASED-LEARNING DAN PEMBELAJARAN LANSUNG TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KELAS X MAN 2 KOTA PALU - Sabri, Sabri; Suyuti, Suyuti; Nuraedah, Nuraedah (Katalogis, 2021)
The problem in this study is whether there is a relationship between the problem-basic-learning model and direct instruction on student learning motivation. This study aims to determine the relationship between the problem-basic-learning model of student learning motivation, the relationship between the direct instruction model and the student learning motivation, and the relationship between the problem-basic-learning model and direct instruction towards the students' learning motivation in history subjects in class X MAN 2, Palu city. This research is a descriptive quantitative research. The population of this research is 250 students. Sampling was done by random sampling. The data collection technique used a questionnaire and documentation. The data analysis technique used was correlation analysis. The results showed that there was a strong relationship between the problem-basic-learning model of learning motivation with a sig value of 0.002, the relationship between direct instruction models and learning motivation also showed a strong relationship with a sig value of 0.048, while the relationship between problem-basic learning models. -learning and direct instruction on history learning motivation obtained a strong relationship with a value of 0.7484.